2014
DOI: 10.4081/ijas.2014.3102
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Maturity and Performance of Pullets Fed Different Preparations and Concentrations of Brown Marine Algae (Sargassum Dentifebium) in Pre-Laying and Early Laying Periods

Abstract: The effect of brown marine algae (BMA; Sargassum dentifebium) as alternative feed source for pullets was studied in three processed and at three concentrations in the pullets from 14-42 weeks. The processing forms were sundried brown marine algae (SBMA), sundried and boiled brown marine algae (BBMA) and sundried and autoclaved brown marine algae (ABMA). The concentrations of BMA were 2%, 4% and 6% that composed 10 treatments along with control. Each treatment was replicated 6 times using 30 pullets per treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Throughout 7 successive laying periods (28 days each) average of laying rate (ALR%), average of egg weight (AEW) were recorded, and total egg mass (TEM) was calculated by multiplying the number of eggs × weight of eggs. Age at sexual maturity was estimated as the number of days from hatching to the day of laying rate 10% egg production as Al-Harthi (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Throughout 7 successive laying periods (28 days each) average of laying rate (ALR%), average of egg weight (AEW) were recorded, and total egg mass (TEM) was calculated by multiplying the number of eggs × weight of eggs. Age at sexual maturity was estimated as the number of days from hatching to the day of laying rate 10% egg production as Al-Harthi (2014).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, BMA increased shell thickness by 3.4% and Haugh unit score by 4.6% of fresh eggs. Moreover, it increased Haugh unit and albumen percentage of stored eggs by 6.1 and 3.5%, (2012) and Al-Harthi (2014), who indicated that BMA can be fed at 3 to 5% in broiler and laying hen diets without adverse effects on productive performance and quality traits of meat and eggs. The positive response of BMA could be attributed to many of the beneficial components found in marine algae, such as vitamins (A, B, B12, C), antioxidants, and antimicrobial substances (Zulkifli et al, 2004;Rimber, 2007;Abd El-Baky et al, 2008;Al-Harthi andEl-Deek, 2011, 2012).…”
Section: General Remarksmentioning
confidence: 99%
“…Moreover, it increased Haugh unit and albumen percentage of stored eggs by 6.1 and 3.5%, (2012) and Al-Harthi (2014), who indicated that BMA can be fed at 3 to 5% in broiler and laying hen diets without adverse effects on productive performance and quality traits of meat and eggs. The positive response of BMA could be attributed to many of the beneficial components found in marine algae, such as vitamins (A, B, B12, C), antioxidants, and antimicrobial substances (Zulkifli et al, 2004;Rimber, 2007;Abd El-Baky et al, 2008;Al-Harthi andEl-Deek, 2011, 2012). Moreover, BMA can be considered as a source of fat and water soluble vitamins, chlorophyll, lutein and zeaxanthin pigments, and an alternative source for n-3 fatty acids (Schiavone et al, 2007;Becker, 2004).…”
Section: General Remarksmentioning
confidence: 99%
See 2 more Smart Citations